PLEASURE OF SPEECH IN THE LANGUAGE STYLE OF THE FRENCH YOUTUBER CYPRIEN - Alicia Nadine Cendekiaputri; Sajarwa Sajarwa; Aprillia Firmonasari (Profetik: Jurnal Komunikasi, 2021)
Language as a part of the study of communication is often used to build individuals' "image," especially amongst people (such as YouTubers) who are well known to the public. In linguistics, one's use of specific language to express oneself is called one's language style. Language styles serve as "signs," through which users create concepts of themselves and their personalities. As such, individuals' language styles usually have specific purposes and functions. This study will examine the language style used by Cyprien, a French media YouTuber, and its functions using the theory of Catherine Fromilhague using qualitative approach. Its corpus draws on data from Cyprien's five most popular videos (as ascertained based on the number of viewers), which were accessed through YouTube media. The data were obtained by viewing these videos and noting the utterances and language styles used. Afterward, data were classified and analyzed based on the language style used and its function. This research finds that eleven language styles were used, with different frequencies. These styles served argumentative, ornamental, and cognitive functions. The conclusion of this study are used to draw viewers' interest and stave off boredom, thereby ensuring that they are willing to follow Cyprien's channel. At the same time, these language styles are used for a range of purposes, including emphasizing essential points and creating rhythm.